Modelling possible effects of strategic nutritional interventions on national N'Dama cattle production in The Gambia - Itty, P. (ILCA/ILRAD, 1988)
Presents the results of an observation and analysis trial carried out to determine the responses of N'Dama cattle to strategic nutritional interventions over a ten-year period using a simulation model of the national cattle herd production.